(untitled) (Web of Discoveries: Journal of Analysis and Inventions, 2025)
This article presents some thoughts on the specific features of teaching comparative pedagogy and the need for its teaching. The article also presents thoughts on the comparative analysis of the education systems of developed countries and the reasons for lagging behind the education systems of some countries.